OC-021 Monocyte oxidative burst defect is associated with susceptibility to infection in severe alcoholic hepatitis. (22nd June 2015) - Vergis, N; Khamri, W; Beale, K; Sadiq, F; Atkinson, S; James, S; Abeles, R; Ryan, J; O'Brien, A; Foxton, M; Wendon, J; Shawcross, D; et al.
Abstract : Introduction: Infection is a common cause of mortality in severe alcoholic hepatitis (SAH). Monocytes are innate immune cells that play a key role in fighting infection. We sought to characterise monocyte phenotype and function in SAH and relate defects to the development of infection. Method: We analysed pre-treatment blood samples from 73 patients admitted to hospital suffering from SAH (DF >32), 34 healthy controls (HC) and 17 abstinent compensated cirrhotic patients (CLD). Flow cytometry was used to measure monocyte phenotype, cytokine production, phagocytosis and oxidative burst ex vivo . Production of superoxide (O2 - ) was measured by luminometry and bacterial killing was assessed by counting viable E. coli colonies growing on agar plates after incubation with monocytes. Additionally, we evaluated the impact of in vivo steroid therapy on monocyte function via the Steroids or Pentoxyfilline for Alcoholic Hepatitis (STOPAH) clinical trial. Results: The proportion of CD14 + + CD16 + + monocytes was increased in SAH and CLD vs HC ( P < 0.003). These cells expressed elevated levels of activation marker HLA-DR ( P < 0.01) and chemokine receptor CCR-5 (.01). In addition, they produced greater TNF-α in response to lipopolysaccharide vs CD14 + + CD16 - cells (.03). Conversely, patrolling CD14 + CD16 + + monocytes were reduced in SAH vs CLD and HC (.01). Phagocytosis was preserved in SAH for all subsets but monocyte oxidative burst (mOB) ( P < 0.001), O2 - production (.02) and bacterial killing (.01) were markedly impaired vs CLD and HC. Importantly, pre-treatment mOB defect predicted the development of infection within the subsequent two weeks of sampling with area under receiver-operator curve of 0.86 ( P < 0.02) (Figure 1 ). Accordingly, defective mOB was associated with death at 28 and 90 days (one-tailed .04 for both). Ex vivo mOB was unchanged in patients who had received 7 days steroid therapy. Conclusion: Defective mOB is prevalent in patients with SAH and is strongly associated with the development of infection within the subsequent two weeks. In addition, CD14 + + CD16 + + monocytes are expanded in SAH and bear features suggestive of an inflammatory role in disease pathogenesis. Further work should seek the molecular mechanisms of these defects and components that might be amenable to therapeutic intervention. Disclosure of interest: None Declared.